2015
DOI: 10.14419/ijh.v3i1.4339
|View full text |Cite
|
Sign up to set email alerts
|

Hematological effects of benzene in the petroleum industry

Abstract: Purpose: To follow up the hematological changes in petroleum workers with continuous exposure to benzene.Approach: The hematological data of two petroleum company male employees was obtained from the annual health check-ups during 2001 to 2005. Workers were classified into exposed and unexposed groups on the basis of their exposure operation performed, and the industrial hygiene surveys.Results: There was not any difference between the exposed and the unexposed groups in the frequency of abnormalities with CBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…(19,24,27) No statistically signi cant difference observed in individuals who were exposed to benzene and non-exposed to benzene regarding Eosinophil counts and TWBCs count, as illustrated in Tables 4, 5. These ndings support previous studies (24,28) regarding increased TWBCs count and contrast with the previous studies (21,25,29) who mentioned decreases in TWBCs count in benzene exposed compared to unexposed controls, and the study (19) who reported increased Eosinophil counts. The difference between recent study results and those of the other studies could be due to the period of exposure to benzene, blood parameters measured, and study design.…”
Section: Categorysupporting
confidence: 90%
“…(19,24,27) No statistically signi cant difference observed in individuals who were exposed to benzene and non-exposed to benzene regarding Eosinophil counts and TWBCs count, as illustrated in Tables 4, 5. These ndings support previous studies (24,28) regarding increased TWBCs count and contrast with the previous studies (21,25,29) who mentioned decreases in TWBCs count in benzene exposed compared to unexposed controls, and the study (19) who reported increased Eosinophil counts. The difference between recent study results and those of the other studies could be due to the period of exposure to benzene, blood parameters measured, and study design.…”
Section: Categorysupporting
confidence: 90%
“…Negative values suggest that the mortality or EMS utilization is concentrated in poor regions while positive values suggest that the mortality or EMS utilization is concentrated in rich regions. A value of 0 means absolute equity among different regions [17]. …”
Section: Methodsmentioning
confidence: 99%